MiR-101 inhibits the proliferation and metastasis of lung cancer by targeting zinc finger E-box binding homeobox 1 - Han, Le (Am J Transl Res, 2018)
MicroRNAs (miRNAs) are involved in the development and progression of lung cancer. MicroRNA-101 (miR-101) displays crucial properties in non-small cell lung cancer (NSCLC) by negatively regulating cell proliferation and invasion, but the underlying molecular mechanisms remain largely unknown. In this study, we found that miR-101 was underexpressed while zinc finger E-box binding homeobox 1 (ZEB1) was highly upregulated in NSCLC tissues and cells. The downregulation of miR-101 was positively associated with lymph node metastasis and poor prognosis of NSCLC patients. Dual-luciferase reporter assay showed that miR-101 directly targeted ZEB1 in NSCLC cells. Enforced expression of miR-101 significantly inhibited NSCLC cell proliferation, apoptosis resistance, migration, and invasion in vitro, which were attenuated by ZEB1 overexpression and phenocopied by ZEB1 knockdown, respectively. Consistently, miR-101 retarded NSCLC growth and metastasis in vivo. The findings indicated that miR-101 suppressed NSCLC growth and metastasis by targeting ZEB1, thereby providing new evidence of miR-101 as a potential therapeutic target for NSCLC patients.